Blockchain Technology Adoption in Malaysia’s e-Government Services: Insights from Case Studies and a Framework for Implementation - Ahmad, Zulaikha; Abdullah , Salfarina (International Journal of Advanced Science Computing and Engineering, 2025)
This paper aims to examine the adoption of blockchain technology within Malaysia’s e-government services, offering empirical insights and a comprehensive framework to guide effective implementation. The primary objectives are to investigate current adoption trends, identify barriers and enablers, and propose a structured approach for policymakers and practitioners. Materials for the research include qualitative data collected from multiple case studies involving key Malaysian government agencies currently piloting or deploying blockchain solutions. Supplementing this, secondary sources such as official government reports and policy documents are analyzed for context. The methodology combines a qualitative case study approach with thematic analysis, allowing for in-depth exploration of implementation processes, stakeholder perceptions, and encountered challenges. Data triangulation ensures the validity and reliability of findings. Results highlight varying degrees of blockchain integration across studied agencies, with primary drivers including a quest for process transparency, improved data integrity, and enhanced public trust. Key challenges are identified as technical infrastructure limitations, regulatory uncertainties, and stakeholder resistance to change. The proposed framework synthesized from case findings emphasizes leadership commitment, capacity building, stakeholder engagement, and iterative pilot testing. The study offers actionable recommendations for government bodies considering blockchain integration and underscores the need for context-sensitive strategies. It concludes with implications for further research, suggesting longitudinal studies to track adoption over time and evaluations of citizen-centric outcomes to refine implementation models.